Transparent Metal Selenide Alloy Counter Electrodes for High‐Efficiency Bifacial Dye‐Sensitized Solar Cells1. Issue 52 (30th October 2014) - Duan, Yanyan; Tang, Qunwei; Liu, Juan; He, Benlin; Yu, Liangmin
Abstract The exploration of cost‐effective and transparent counter electrodes (CEs) is a persistent objective in the development of bifacial dye‐sensitized solar cells (DSSCs). Transparent counter electrodes based on binary‐alloy metal selenides (M‐Se; M=Co, Ni, Cu, Fe, Ru) are now obtained by a mild, solution‐based method and employed in efficient bifacial DSSCs. Owing to superior charge‐transfer ability for the I−/I3− redox couple, electrocatalytic activity toward I3− reduction, and optical transparency, the bifacial DSSCs with CEs consisting of a metal selenide alloy yield front and rear efficiencies of 8.30 % and 4.63 % for Co0.85Se, 7.85 % and 4.37 % for Ni0.85Se, 6.43 % and 4.24 % for Cu0.50Se, 7.64 % and 5.05 % for FeSe, and 9.22 % and 5.90 % for Ru0.33Se in comparison with 6.18 % and 3.56 % for a cell with an electrode based on pristine platinum, respectively. Moreover, fast activity onset, high multiple start/stop capability, and relatively good stability demonstrate that these new electrodes should find applications in solar panels.